Selfitis and motivation for self-portrayal among young Nigerians - Olanrewaju O. Akinola; Akintayo A. Ogunsanya; Oluwakemi D. Okunade; Ibrahim A. Adekunle (African Governance and Development Institute (AGDI), 2020)
Since contemporary technological developments led to an explosion in different media of communication allowing individuals to actively create and publish whatever content they desire, scholars have been investigating trends, activities and implications thereof linked to this advancement. Whereas the literature on selfie is robust, little is known about motivations for taking selfies from a Nigerian perspective. Yet, the rate at which young Nigerians take and share selfies is both intense and passionate suggesting possible obsession, warranting the need to investigate if this critical segment of the national population is aware and mindful of mental illnesses associated with compulsive and excessive selfie-taking and sharing. Consequently, this study investigated motivations that drive young Nigerians' selfie-taking and sharing habit, including gender disparity associated with the activity. A total of 487 questionnaires and 21 interviews, administered on young Nigerians between the ages of 16 and 24 from two tertiary institutions revealed that a substantial number of young Nigerians take, store and share selfies habitually. The study established that young female Nigerians take more selfie than their male counterparts while there is no gender disparity noticed in sharing. An overwhelming majority (85.7 percent) confessed to being obsessed with selfie-taking and sharing, while a corresponding percentage of respondents are not aware of the health-related dangers associated with the activity. In the light of these findings, coupled with the increasing rate of depression and suicide among young people, we conclude that the Selfitis disposition observed in a sizeable percentage of young Nigerians is ill-motivated and requires some urgent intervention.
Keywords: 330; Selfitis; Obsession; Selfie; Nigeria